Literature review: Safety aspects and halal status of Kombucha - Feni Mustika Sari; Riskia Chandra Widianti; Mochamad Fajar Deliaz; Akbar Rizqi Kurniawan (Nur Science Institute, 2026)
Kombucha is a fermented tea beverage produced by a symbiotic culture of bacteria and yeast (SCOBY) and is increasingly consumed as a functional beverage. However, concerns regarding its safety and halal status remain, particularly due to ethanol formation during fermentation. This review aimed to evaluate the safety aspects and halal compliance of Kombucha by analyzing fermentation conditions, microbial activity, alcohol production, and halal critical control points. A literature review approach was employed using scientific articles, conference proceedings, fatwas, and official regulatory documents retrieved from PubMed, ScienceDirect, and Google Scholar. The findings revealed that fermentation temperature, pH, duration, substrate composition, and microbial diversity significantly affected kombucha quality, particularly ethanol concentration and microbiological safety. Kombucha was generally considered safe for healthy individuals when produced under hygienic, controlled conditions. In contrast, uncontrolled fermentation increased the risk of excessive alcohol formation and microbial contamination. From a halal perspective, Kombucha may be considered permissible when ethanol content remains below 0.5%, and all ingredients and processing stages comply with halal requirements. Therefore, standardized fermentation control and halal assurance practices are essential to ensure product safety and halal compliance.